Analgesia in the Emergency Department for Lower Leg and Knee Injuries: A Case Report - Michael Shalaby; Yonhoon Lee; Joseph McShannic; Michael Rosselli (Clinical Practice and Cases in Emergency Medicine)
Introduction: Lower extremity injuries are commonly evaluated and treated in the emergency department (ED). Pain management for these injuries often consists of acetaminophen, non-steroidal anti-inflammatories, and opioids. Despite this treatment regimen, adequate analgesia is not always achieved. Case Report: A 38-year-old man presented to the ED with a non-displaced tibia-fibula fracture. The patient did not attain analgesia with intravenous medications but did get complete anesthesia of his lower leg with a combination saphenous and popliteal sciatic nerve block. Conclusion: Emergency physicians possess the skill set required to effectively perform a saphenous and popliteal sciatic nerve block and should consider adding this procedure to their armamentarium of pain management techniques in treating injuries distal to the knee.